Environmental Benefits of Palm Oil Biodiesel Enhancement: Urea Complexation Optimization via RSM - Helwani, Zuchra; Amraini, Said Zul; Abd Rahman, Sunarti; Zahrina, Ida; Julhijah, Noni; Ulfaa, Suci Mas’ama (Heca Sentra Analitika, 2024)
Indonesian commercial biodiesel products are unstable due to polyunsaturated fatty acids (PUFA). The urea inclusion compound (UIC) method is used during the fractionation process on PUFA to enhance its quality. This study aims to determine the effect of temperature, fatty acid ester metal (FAME)/methanol ratio, and crystallization time on increasing the concentration of PUFA concentrates and to produce high-performance biodiesel products with an iodine indicator <30–40 g I2/100 g. According to the most recent research, the UCF phase product is obtained at a combination of temperature and crystallization time of 20 °C and 4 h, respectively. It has an iodine number of 44.01 and an oxidation stability of 18.61 h, which is close to the criteria for high-performance biodiesel (<30 –40 g I2/100 g). Meanwhile, the results of this study obtained a UCF phase product that has an iodine number of 34.18 and yields 86.57% is obtained at a combination of temperature and crystallization time of 20 °C and 6 hr and FAME-methanol ratio of 6, respectively, which is close to the criteria for high-performance biodiesel (<30 –40 g I2/100 g). The longer complexation time and temperature significantly affected the FAME fractionation of the UCF phase.